Trifoliation-a New Freak in Ficus Krishnae C. de C. - Vaid, K. M. (Indian Forester, 1963)
In the beginning of the present century Ficus krishnae came to be Hnown as a botanical Curiosity and connected with mythology because of the peculiar cup-shaped modification -of the leaves. Added to this, a new freak, in the shape of the presence of leafy appendages on the petiole has now been observed. This again is a very rare occurrence not to be met with in any of the allied genera or species.